The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.20965/jdr.2012.p0682
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of S-Wave Velocity Profiles and Site Amplification Around the K-NET Tsukidate Station, Miyagi Prefecture, with Reference to Large PGA During the 2011 off Pacific Coast of Tohoku Earthquake, Japan

Abstract: In this study we investigated site amplifications in shallow soil around Tsukidate station (MYG004) of KNET in Miyagi prefecture with a seismic intensity of 7 during the 2011 off the Pacific Coast of Tohoku Earthquake from aftershock observation and microtremor explorations. We conducted aftershock observations by installing 8 temporary stations. We estimated site amplifications of S-wave from the observed data. We found that the predominant period of amplification at a site near MYG004 was 0.2 seconds. The am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…2c clearly shows that SBSR01~04 significantly underestimate SBSR05 (ETF), suggesting that neglecting deep velocity variations causes a considerable underestimation of site responses at both low and, more interestingly, high frequencies although downward waves may also be somewhat responsible. Our empirical evidence is consistent with the numerical results by Yamanaka et al [22]. Therefore, only when there is no abrupt impedance contrast (IC) below the downhole sensor at a site, can SBSR be used as its ETF.…”
Section: Empirical Transfer Function (Etf)supporting
confidence: 91%
See 1 more Smart Citation
“…2c clearly shows that SBSR01~04 significantly underestimate SBSR05 (ETF), suggesting that neglecting deep velocity variations causes a considerable underestimation of site responses at both low and, more interestingly, high frequencies although downward waves may also be somewhat responsible. Our empirical evidence is consistent with the numerical results by Yamanaka et al [22]. Therefore, only when there is no abrupt impedance contrast (IC) below the downhole sensor at a site, can SBSR be used as its ETF.…”
Section: Empirical Transfer Function (Etf)supporting
confidence: 91%
“…It is expected that deep velocity structures affect the amplification spectra in the low-frequency range. However, using a numerical approach, Yamanaka et al [22] showed that deep velocity configurations could influence the amplifications at high frequencies as well. When the underlying layer having higher 𝑉 is removed, the levels of amplification at high frequencies are lower than those of the complete model.…”
Section: Empirical Transfer Function (Etf)mentioning
confidence: 99%